World wide research : reshaping the sciences and humanities - Dutton, William H., 1947-; Jeffreys, Paul W., 1954- (MIT Press, 2010)
Here, experts examine ways in which the use of increasingly powerful and versatile digital information and communication technologies are transforming research activities across all disciplines.